Experimentalism photo club: from geraldo de barros photo forms until the urban decay of carlos navarro (Palíndromo, 2015)
The clubber photography has a tradition praise of the way through the technical care, but during the modern period it goes through constant attempts to reframe the photographic doings in order to make it more comprehensive. Aiming at the trial study in photo clubs in Manaus, this article proposes to car- ry out a comparative study between the works of two photographers: Carlos Na- varro and Geraldo de Barros, articulating the possible aesthetic dialogues between them, regardless of temporality and ter- ritoriality. The analysis of visual elements and interpretative possibilities suggested in the images will be based on the stud- ies of Boris Kossoy, Costa e Silva, Junior Fernandes and Lima. Thus an image of photo forms series of Geraldo de Barros (1923-1998) and another image of the trial Urban Decay Carlos Navarro were elected (1945), both developed during part of clubber period of photographers. Similarities and singularities have been observed as regards the aesthetic, tech- nical, control, “error”, and reception of works. Finally, it was found that the art- ists studied each contributed in their own way, with the subversion of the photo- graphic code when crossing the para- digms within the context in which their production was developed.
Keywords: Geraldo de Barros; Carlos Navarro; photo club; experimentalism; modernity